2018
DOI: 10.1038/s41598-018-33882-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of partial molar enthalpy of oxides on Soret effect in high-temperature CaO–SiO2 melts

Abstract: The Soret effect or thermodiffusion is the temperature-gradient driven diffusion in a multicomponent system. Two important conclusions have been obtained for the Soret effect in multicomponent silicate melts: first, the SiO2 component concentrates in the hot region; and second, heavier isotopes concentrate in the cold region more than lighter isotopes. For the second point, the isotope fractionation can be explained by the classical mechanical collisions between pairs of particles. However, as for the first po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…On the whole, the S T quantity would be declining if the thermal gradient was increasing gradually. In addition, three other works also reported that: if a multicomponent system was under an effect of a thermal gradient, then lighter fractional elements would concentrate in the hot region, while heavier elements would concentrate in the cold one. According to them, qualitatively, trends of the SC quantity versus the temperature difference, and trends of molecular migrations under influences of the thermal gradient on the SET systems here, would be in good agreement with those of the experimental observations.…”
Section: Resultsmentioning
confidence: 99%
“…On the whole, the S T quantity would be declining if the thermal gradient was increasing gradually. In addition, three other works also reported that: if a multicomponent system was under an effect of a thermal gradient, then lighter fractional elements would concentrate in the hot region, while heavier elements would concentrate in the cold one. According to them, qualitatively, trends of the SC quantity versus the temperature difference, and trends of molecular migrations under influences of the thermal gradient on the SET systems here, would be in good agreement with those of the experimental observations.…”
Section: Resultsmentioning
confidence: 99%
“…The diamond wheel had a thickness of 0.3 mm. The loss of glass during these processes was estimated to be 0.2 ± 0.25 mm 17 …”
Section: Methodsmentioning
confidence: 99%
“…The loss of glass during these processes was estimated to be 0.2 ± 0.25 mm. 17 We measured the composition of the glass of each slice using confocal Raman spectroscopy (LabRAM HR Evolution, HORIBA).…”
Section: Determination Of the Compositionsmentioning
confidence: 99%
“…26) The author and coauthors compared the Soret coefficient calculated by nonequilibrium molecular dynamics (NEMD) with that by adjusted Kempers mode [Eq. (12)] 17) in the CaOSiO 2 melts. In the NEMD, the interionic potential proposed by Seo et al 27) was employed because the potential parameter sets can reproduce structures and thermodynamic parameters well.…”
Section: Verification With Numerical Simulationmentioning
confidence: 99%